RISK OF DEVELOPING SUBCLINICAL HYPOTHYROIDISM AMONG INDIVIDUALS WITH TSH VALUES 2.5-4.2 mIU/L - (:unkn) unknown (NOBEL ILAC, 2016)
Objective: Estimating the serum thyroid stimulating hormone (TSH) concentration is the most sensitive test to show thyroid function. TSH values of 95 percent of the population fall between 0.3-2.5 mIU/L. Although lower limits of the reference interval is certain, upper limits remains controversial. Research data indicate that individuals with TSH values outside the 2.5-3.0 mIU/L interval are under risk for thyroid disorders. The purpose of this study is to investigate the time dependent subclinical hypothyroidism risk of the individuals with TSH values over 2.5 mIU/L. Material and Method: The research is composed of three groups including healthy subjects with TSH values between 0.27-2.5 mIU/L (n=55) with negative thyroid peroxidase antibody (TPO Ab) and thyroglobulin antibody (TG Ab) values and cases with TSH values between 2.5-4.2 mIU/L and with positive (60) and negative (n=212) anti-TPO and anti-TG levels. The data are surveyed retrospectively and the difference between the past and present TSH levels are investigated. For statistical analysis paired and unpaired t-test is used. Results: In all groups statistically meaningful elevation of time dependent TSH values were found. While in the group with TSH values between 2.5-4.2 mIU/L and negative thyroid antibodies the risk of subclinical hypothyroidism was calculated as 23% for the first 5 years, for the group with positive antibodies it was found to be 30%. TSH values 0.27-2.5 mIU/L no subclinical hypothyroidism was evident in 5 years of duration. Conclusion: The results showed that individuals with TSH values between 2.5-4.2 mIU/L are under risk for subclinical hypothyroid independent of thyroid antibody concentration.
Keywords: Subclinical hypothyroidism; TSH reference interval; TPO Ab; TG Ab; THYROTROPIN REFERENCE RANGE; THYROID-DISEASE; REFERENCE INTERVALS; FOLLOW-UP; ULTRASONOGRAPHY; ASSOCIATION; DYSFUNCTION; POPULATION; ANTIBODIES; COMMUNITY